Aerobic biodegradation of butanol and diesel oil blends - Mariano, Adriano Pinto [UNESP]; Tomasella, Richard Clayton [UNESP]; Di Martino, Clara; Morais, Eduardo Beraldo; Maciel Filho, Rubens; Regali Seleghim, Mirna Helena; Contiero, Jonas [UNESP]; Tauk Tornisielo, Samia Maria [UNESP]; de Angelis, Dejanira de Franceschi [UNESP] (Academic Journals, 2010)
This work aimed to evaluate the aerobic biodegradation of butanol/diesel oil blends (5, 10, 15, 20%, v/v) in comparison to the biodiesel/diesel oil blend (20%, v/v). Respirometric experiments simulating the contamination of natural environments (soil and water from a river) were carried out in biometer flasks (250 mL) used to measure microbial carbon dioxide (CO(2)) production. The automated turbidimeter Bioscreen C was used to follow the growth of Pseudomonas aeruginosa LBI on butanol/diesel oil blends. A redox indicator (2,6-dichlorophenol indophenol - DCPIP) test was used to evaluate the capability of four inocula to biodegrade the blends with 20% (v/v). The experiment which simulated the soil contamination demonstrated that butanol is less biodegradable than diesel oil, and for this reason the increase in the portion of butanol in the butanol/diesel blend from 5 to 20% had negative effects on biodegradation. While in soil the biodiesel/diesel blend was more easily biodegraded than the butanol/diesel blend, in water this order was the inverse. The insoluble fuels (diesel and biodiesel) were poorly biodegraded in water and the biodegradation of the butanol/diesel blend was favored by the water solubilization of the butanol, which enhances the bioavailability of this compound. on the other hand, initial concentrations of butanol in the water higher than 10 mL L(-1) inhibited the cell growth of the tested microorganisms. Thus, butanol toxicity presumably had a significant effect on the degree of biodegradation of the fuel blends.
Keywords: Butanol; biodiesel; diesel; biodegradation; blends; soil; water